2002
DOI: 10.1046/j.1440-1703.2002.00458.x
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐hemispheric comparison of bottom‐up effects on community structure: Insights revealed using the comparative‐experimental approach

Abstract: The comparative‐experimental approach uses identically designed, replicated experiments at different sites along environmental gradients in order to gain insight into the changing dynamics of communities with changing environmental conditions. Such studies reveal how ecological processes vary in intensity and interact to produce community structure. Early emphases were on the community consequences of shifting top‐down impacts, competition and disturbance with environmental stress. Recent advances include the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 62 publications
8
75
2
Order By: Relevance
“…Indeed one of the few comparative ecological studies across the Atlantic demonstrated the strong effects of productivity in mediating the effects of consumers on local diversity (Worm et al 2002). Despite the recognition of the importance of productivity there have been few attempts to relate larger-scale patterns in community structure to inter-regional differences in productivity (but see Bustamante et al 1995, Menge et al 2002, Worm et al 2002. Global images of ocean color show consistent areas of high and low pelagic productivity along the coastlines of America and Europe, but no clear overall differences between the two regions (images available online).…”
Section: Inshore Pelagic Productivitymentioning
confidence: 99%
“…Indeed one of the few comparative ecological studies across the Atlantic demonstrated the strong effects of productivity in mediating the effects of consumers on local diversity (Worm et al 2002). Despite the recognition of the importance of productivity there have been few attempts to relate larger-scale patterns in community structure to inter-regional differences in productivity (but see Bustamante et al 1995, Menge et al 2002, Worm et al 2002. Global images of ocean color show consistent areas of high and low pelagic productivity along the coastlines of America and Europe, but no clear overall differences between the two regions (images available online).…”
Section: Inshore Pelagic Productivitymentioning
confidence: 99%
“…Lubchenco and Menge wanted to probe other environmental impacts on coastal ecosystems, and so began a decades-long world tour that took Paine's experimental approaches to Chile, South Africa and New Zealand. Their studies showed 4 , for example, that the intermittent upwelling of nutrient-rich water can intensify competition, predation and other interactions between marine species.…”
Section: Growing Ecosystemmentioning
confidence: 99%
“…This experiment was therefore started to examine micro and medium scale variability of grazing and the influence of slow moving and fast moving consumers in tropical rocky shore algal communities at Cape d' Aguilar and Stanley shores, Hong Kong. It is hoped that by separating the effects of different consumer groups using the comparative experimental approach (Dayton 1971;Menge 1986a;Menge 1999;Menge et al 2002) this will help us identify the major groups of consumers and species that can directly or indirectly impact the settlement, growth and distribution of algae. This approach allows us to directly compare sites, shores and treatments over a large area and to generalize results to similar shores.…”
Section: Objectives Of the Researchmentioning
confidence: 99%